PENGARUH TINDAKAN SUPERVISI, PENGALAMAN KERJA, KOMITMEN ORGANISASI DAN KOMITMEN PROFESIONAL TERHADAP KEPUASAN KERJA AUDITOR (Studi Empiris pada Kantor Akuntan Publik Pekanbaru, Padang, dan Medan) - Fitriyanti, Rika; Nasir, Azwir; Diyanto, Volta (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study was aimed to examine the effect of supervisory action, work experience, organizational commitment and professional commitment to job satisfaction of auditors. In this study, data collected by using questionnaires given to auditors who work in Public Accounting Firm in Pekanbaru, Padang and Medan. From questionnaires distributed as much as 120 questionnaires (82%) and can be completed and processed. Data collected were analyzed by using partial least squares (PLS) version 2.0 m3 which comparing t-statistics value generated from the output of PLS with t-table value. PLS output is estimated latent variables that are linear aggregates of indicators with a significance equal to 0,05 or 5%. The results of this study indicate that the action of supervision and organizational commitment has no effect to the job satisfaction of auditors. While work experience and professional commitment effect to the job satisfaction auditors.Keywords: supervisory action, work experience, organizational commitment, professional commitment, and job satisfaction auditors.